Civil drafting technology - Madsen, David A. (Prentice Hall Career & Technology, 1994)
Civil Drafting Technology Seventh Edition covers it all-basic and advanced topics-and everything in between, equipping readers to convert engineering sketches or instructions into actual formal drawings and gain a working knowledge of mapping. Using a "knowledge building" format where one concept is mastered before the next is introduced, Civil Drafting Technology includes: